Two-period pricing and strategy choice for a supply chain with dual uncertain information under different profit risk levels. (October 2019) - Liu, Zhibing; Gao, Rong; Zhou, Chi; Ma, Nana
Highlights: A concept of PRLS is proposed to depict the profit risk caused by uncertain demand. The retail price in period 2 is lower than that in period 1 for a give PRLS. The retail price in period 2 is convex on PRLS contrary to intuition. Differential pricing of supplier with stage pricing response of retailer is best. The suggested optimal PRLS shows expectation criterion is not always appropriate. Abstract: With the rapid development of e-commerce and Internet technology, multi-period dynamic pricing is a natural choice that conforms to the demand trend of customers who make product purchase decisions based on current prices, past observed prices (reference prices) and past product reviews in a repeated market. This study considers a problem of two-period pricing and strategy choice for a supply chain consisting of a supplier and a retailer in the presence of uncertain basic market demand and uncertain product review. The supplier adopts a price commitment or differential pricing strategy and the retailer responds with a stage pricing or first-period pricing strategy, which constitutes four strategies. A concept of the profit risk level of a supply chain (PRLS) is proposed to characterize the profit risk of the supply chain due to dual uncertain information. Under the four strategies and different PRLSs, we find that the retailer prefers to set a lower retail price in the second period than in the first period to obtain more profits. Interestingly, although the profits of participants in the supply chain increase with the PRLS, the retail price in the second period is convex about the PRLS, which is contrary to the intuition that high risks imply high prices. Furthermore, our results reveal that the strategy under which the supplier uses a differential pricing strategy and then the retailer responds with a stage pricing strategy is the best under the four strategies for a given PRLS because it is win-win for the supplier and retailer. Finally, an optimal PRLS is suggested to balance the profits and risks, which shows that the expectation is not always an appropriate decision rule.